Pengembangan Rumah Imunisasi dengan My Board in the Village - Naimah, Naimah; Triningsih, Reni Wahyu; mas'udah, endah kamila (Politeknik Kesehatan Kemenkes malang, 2023)
Complete basic immunization is an immunization organized by the government which aims to improve the health status of infants in Indonesia, which is given starting from infants aged 0 to. 18 months. The data shows that the complete basic immunization coverage in Malang Regency is still below the minimum target. The success of fulfilling this coverage cannot be separated from the role of health kader as a bridge between health workers and immunization targets in particular. This community service aims to socialize and train health kader in using the